Place of carbocysteine in the treatment of acute respiratory viral infections and bronchitis in therapeutic practice - A. L. Vertkin; M. M. Shamuilova; G. Yu. Knorring (Лечащий Врач)
In the structure of morbidity in the Russian Federation, respiratory system diseases are in the lead, among which acute respiratory viral infections and bronchitis are make up the majority, as well the leaders in the number of disability cases. The respiratory tract damage mechanisms in viral infections are diverse and require the use of a wide range of drugs. The pathology of the respiratory system in the vast majority of cases is accompanied by the development of cough as a key syndrome, reflecting the severity of the respiratory system, and the tension of the defense systems. When an infectious agent (usually a viral etiology) enters the respiratory system, several pathways for the formation of a pathological cough are triggered: inflammation products have a trigger effect on bronchial chemoreceptors, increasing the sensitivity of all cough receptors, causing expansion of mucosal microvessels, hypersecretion of glands. A violation of mucociliary clearance becomes inevitable along with changes in the volume and viscosity of sputum, which further aggravates the severity of cough and the patient's condition. The use of mucociliary transport stimulants is justified by their most important theirproperties. Carbocysteine, in addition to long-known effects (mucoregulatory, mucolytic, the ability to improve mucociliary transport), also has anti-inflammatory, immunomodulatory and antioxidant effects, which determines its importance in the acute respiratory viral infections and bronchitis treatment. Carbocisteine is recognized by the Russian Respiratory Society, the Scientific and Practical Council of the Ministry of Health of the Russian Federation, the National Medical Association of Otorhinolaryngologists, the Russian Union of Pediatricians as an effective active ingredient for the treatment of diseases of the upper and lower respiratory tract, which is reflected in the relevant modern recommendations of the Ministry of Health for the treatment of bronchitis in children, chronic bronchitis in adults, chronic obstructive pulmonary disease, acute sinusitis and acute otitis media in children and adults. The use of drugs with new pharmacological characteristics improves patient compliance.